1991
DOI: 10.1203/00006450-199108000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Birth-Related Events on Metabolism in Fetal Sheep

Abstract: ABSTRACT. At birth, changes in utilization of metabolic substrates occur as the fetus, dependent upon carbohydrates and amino acids available continuously from the placenta, becomes a neonate, dependent primarily upon fat obtained intermittently by suckling. In addition to changes in substrates, at birth, metabolic rate increases dramatically as the activity of several organs and thermoregulatory mechanisms increase. To determine whether metabolic changes are related to certain events that occur at birth, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, as mentioned above, based on the studies in fetal lambs, increasing oxygen concentration in cerebral arterial blood results in vasoconstriction with reduction in cerebral blood flow. 17 Although cerebral oxygen delivery and consumption are maintained, glucose delivery and consumption are markedly reduced. The reduction in substrate could interfere with cerebral development, despite an adequate oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as mentioned above, based on the studies in fetal lambs, increasing oxygen concentration in cerebral arterial blood results in vasoconstriction with reduction in cerebral blood flow. 17 Although cerebral oxygen delivery and consumption are maintained, glucose delivery and consumption are markedly reduced. The reduction in substrate could interfere with cerebral development, despite an adequate oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the effect of acute change in oxygen saturation on cerebral blood flow and metabolism. 17 Fetal sheep were prepared with indwelling vascular catheters and a tracheal tube. After recovery for 2-3 days studies were conducted on the fetuses in utero; blood flows to organs were measured by the radionuclide-labeled microsphere technique.…”
Section: Chronic Maternal Hyoeroxia To Improve Left Ventricular and Amentioning
confidence: 99%
“…One study reported that chronic MH may be associated with growth restriction (63), whereas another group had concerns regarding fetal brain and placental development (16). In animal models using fetal sheep it could also be shown that hyperoxygenation led to reduced cerebral perfusion resulting in significantly decreased cerebral glucose delivery and consumption (68). Other fetal complications like constriction of the arterial duct or retinopathy may also be considered but were not reported in human studies on chronic MH.…”
Section: Maternal Hyperoxygenation Therapy To Stimulate Left Heart Gr...mentioning
confidence: 99%